If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 66 = 360 Reorder the terms: 66 + 3x = 360 Solving 66 + 3x = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-66' to each side of the equation. 66 + -66 + 3x = 360 + -66 Combine like terms: 66 + -66 = 0 0 + 3x = 360 + -66 3x = 360 + -66 Combine like terms: 360 + -66 = 294 3x = 294 Divide each side by '3'. x = 98 Simplifying x = 98
| 3u-5=8u-28+8 | | A^2(5a+2)(a+2)=0 | | X^2+4x-6=12 | | 8=3m-16 | | k^3-k^2-4k+4=0 | | x^2+5x-6=12 | | X-3=180 | | -13=y-4 | | x^4+5x-6=12 | | (3.250+2.75)*2= | | (+6+-2)*-3= | | a-(2-5a)=4 | | 5.5r+7.2m=-12 | | .10*27000= | | if-6b=54thenbis | | 5x+20=360 | | x^4+5x-6=8 | | 1.12x=y-120 | | 6x+1+45+4x-6=180 | | x(3x+17)=-20 | | 1.12x=y-115 | | -390y+1000y=4880 | | 1.12x=y-110 | | 2x-9+12x+3x-21=-40 | | 6n+4k-4n= | | 2x+9+12x+3x-21=40 | | 8a+-28b+15c= | | 100p^2=334.08 | | 2x-9+12x+3x-21=40 | | f(x)=6*6-4 | | 6x^2+19x-12=0 | | 1.12x=y-105 |